Respuesta :
i told u rem is not best girl
f(x) = 2(3)^{x+1} + 4
vertical stretch f(x) by a scale factor of a is a * f(x)
so yeah
g(x) = 2 * f(x)
[tex]g(x) = 2 * (2(3)^{x+1} + 4)[/tex]
g(x) = 4(3)^(x+1) + 8 (distributed)
f(x) = 2(3)^{x+1} + 4
vertical stretch f(x) by a scale factor of a is a * f(x)
so yeah
g(x) = 2 * f(x)
[tex]g(x) = 2 * (2(3)^{x+1} + 4)[/tex]
g(x) = 4(3)^(x+1) + 8 (distributed)
Answer:
The equation of g(x) is, [tex]4(3)^{x+1} +8[/tex]
Step-by-step explanation:
Given the function: [tex]f(x) = 2(3)^{x+1} + 4[/tex]
Vertically stretch states that if y = f(x), then y =a f(x) gives a vertical stretch when a> 1.
It is given that the graph of f(x) is stretched vertically by a factor of 2 to form the graph of g(x)
then by definition of vertical stretch we have;
[tex]g(x) = 2f(x)[/tex] as 2> 1
Then, g(x) becomes = [tex]2 (2(3)^{x+1} + 4)[/tex] = [tex]4(3)^{x+1} +8[/tex]
Therefore, the equation of g(x) is, [tex]4(3)^{x+1} +8[/tex]